LAYANAN KONSELING TERHADAP KESALAHPAHAMAN DALAM MEMAKNAI KOMUNIKASI NON VERBAL (PESAN KINESIK) DI LINGKUNGAN ASRAMA - Yusrain (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2019)
The relationship between non-verbal communication (kinesic messages) and children's adjustment is that non-verbal communication such as facial expressions, body movements, and eye contact greatly influence the process of interacting with fellow humans. Especially for the first time face to face and interact with each other. So that sometimes the habits of these movements greatly influence social interaction. Especially if those interacting are from different cultural backgrounds. So that there are misunderstandings in understanding the non-verbal communication messages, such as kinesics. The counseling services that the author can offer in dealing with this problem can use several counseling services, including rational emotive and behavioristic therapy.